Sustainable waste management in the construction industry - Shajidha, Hafsa; Mortula, Md Maruf (Frontiers in Sustainable Cities, 2025)
The sustainability of the construction industry largely depends on effective waste management practices throughout both construction and demolition processes. Construction and demolition waste causes significant environmental degradation, resource depletion, and landfill overflow, making effective waste management an essential component of sustainable construction practices. As the construction industry is one of the biggest contributors of generated waste in today’s world, achieving sustainability in this industry is essential for overall sustainable development. This study aims to examine the sustainable approach to construction and demolition waste and develop strategies for the industry. Based on the evaluation of various waste management techniques, this study used a standard approach in examining existing literature available in renowned research databases and key concepts to develop strategies for future construction and demolition waste management. This included identifying appropriate keywords or combining multiple keywords during the search process. Waste reduction and protecting the planet’s precious natural resources have been the focus of this study. This research investigated strategies during the planning and design phases. Out of the three strategies tested; reduction at the source, recycling, and reuse, source reduction yields the best results. Selecting materials, optimizing designs, and improving processes are all essential techniques for source reduction. Additionally, it explores the role of policy interventions and regulatory frameworks in improving source reduction practices across the industry. However, as waste reduction may not always eliminate waste generation, especially during the demolition of buildings, it is important to supplement this with existing recycling and reuse approaches. With the use of alternative building materials, it is essential to reassess recycling and reuse options for innovative and sustainable construction materials. The findings illustrate that efficient waste reduction regulations, such as green building certifications and mandatory waste management plans, are critical to achieving sustainability. By incorporating source reduction measures in addition to recycling and reuse of waste management, the construction may drastically minimize its environmental effect while increasing cost efficiency and resource usage. This study emphasizes that source reduction should be mandatory for accomplishing sustainable construction and demolition waste management. Recycling and reuse should complement waste reduction efforts.